A modelling study of the atmospheric chemistry of DMS using the global model, STOCHEM-CRI. (February 2016) - Khan, M.A.H.; Gillespie, S.M.P.; Razis, B.; Xiao, P.; Davies-Coleman, M.T.; Percival, C.J.; Derwent, R.G.; Dyke, J.M.; Ghosh, M.V.; Lee, E.P.F.; Shallcross, D.E.
Abstract: The tropospheric chemistry of dimethylsulfide (DMS) is investigated using a global three-dimensional chemical transport model, STOCHEM with the CRIv2-R5 chemistry scheme. The tropospheric distribution of DMS and its removal at the surface by OH abstraction, OH addition, NO3 oxidation, and BrO oxidation is modelled. The study shows that the lifetime and global burden of DMS is ca. 1.2 days and 98 Gg S, respectively. Inclusion of BrO oxidation resulted in a reduction of the lifetime (1.0 day) and global burden (83 Gg S) of DMS showing that this reaction is important in the DMS budget. The percentage contribution of BrO oxidation to the total removal of DMS is found to be only 7.9% that is considered a lower limit because the study does not include an inorganic source of bromine from sea-salt. BrO oxidation contributed significantly in the high latitudes of the southern hemisphere (SH). Inclusion of DMS removal by Cl2 showed that potentially a large amount of DMS is removed via this reaction specifically in the remote SH oceans, depending on the flux of Cl2 from the Southern Ocean. Model DMS levels are evaluated against measurement data from six different sites around the globe. The model predicted the correct seasonal cycle for DMS at all locations and correlated well with measurement data for most of the periods. Highlights: The lifetime and global burden of DMS is found to be 1.2 days and 98 Gg S yr −1 . Inclusion of BrO oxidation reduces the lifetime and global burden of DMS by 15%. The removal of DMS by Cl2 is found to be high over the southern hemisphere oceans. Model DMS shows a seasonal trend with summer maximum and winter minimum.